Projecting Demand for Skilled Foreign Labor and Meeting Skills Shortages : Selected Country Approach - Irving, Jacqueline (World Bank, Washington, DC, 2013)
Policy makers apply skilled labor gap projections to their immigration policies in a number of ways including: differentiating immigration policies by region, based on skills supply and demand mismatches; introducing more flexibility in admissions policies to acquire specific skills; and designing programs to actively attract immigrants with specific needed skills to specific occupations. Challenges in projecting an economy's demand for skilled foreign labor may include bias and gaps in available data sources, as well as difficulty determining the most appropriate methodology and impediments posed by imperfect methodological assumptions. A difficult economic context may provide further challenges to projecting and filling foreign labor needs.